2018
DOI: 10.18203/2320-6012.ijrms20185359
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between 6-minute walk distance and spirometry parameters in stable chronic obstructive pulmonary disease patients

Abstract: Background: Six minute walk test (6MWT) is a sub-maximal exercise test, used as a clinical indicator of the functional capacity, in patients with cardiopulmonary diseases. It is simple, objective and reproducible test. The present study was designed to assess correlation of six minute walk test with spirometry parameters, in patients with chronic obstructive pulmonary disease.Methods: In this cross sectional study, fifty patients diagnosed with chronic obstructive pulmonary disease (GOLD criteria) coming to te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…In another study that involved both European and American subjects, the proportion of females was 36.7% among Europeans and 33.3% among Americans, which is in accordance with our findings [ 9 ]. A study by Hajare et al reported a male-to-female ratio of 2.3:1 [ 10 ]. The preponderance of males being affected can be attributed to the fact that males are more involved in outdoor activities and hence are more exposed to environmental pollutants [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…In another study that involved both European and American subjects, the proportion of females was 36.7% among Europeans and 33.3% among Americans, which is in accordance with our findings [ 9 ]. A study by Hajare et al reported a male-to-female ratio of 2.3:1 [ 10 ]. The preponderance of males being affected can be attributed to the fact that males are more involved in outdoor activities and hence are more exposed to environmental pollutants [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, other factors such as poorly controlled chronic asthma, occupational exposures to dusts and smokes, and malnutrition should also be considered. 16,17 A greater part of the study group had a normal BMI (63 [53.38%]). The FEV 1 was calculated to be the least in patients with a BMI < 18.5 kg/m 2 and the highest in the BMI group of 25 to 29.9 kg/m 2 .…”
Section: Discussionmentioning
confidence: 99%
“…However, other factors such as poorly controlled chronic asthma, occupational exposures to dusts and smokes, and malnutrition should also be considered. 16 17…”
Section: Discussionmentioning
confidence: 99%